2007
DOI: 10.1016/j.chemosphere.2006.05.084
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of ambient air PCDD/F levels in Portugal

Abstract: As part of a monitoring program conducted by IDAD -Institute for Environment and Development and supported by regional municipal solid waste (MSW) management authorities, dioxin concentrations in ambient air were measured in three regions of Portugal: Porto, Lisbon and Madeira. These independent studies were performed with the intention of providing data as a basis for the evaluation of potential impacts of the operation of recently built MSW incinerators. Thus, 170 samples were collected in nine different sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 7 publications
1
20
0
1
Order By: Relevance
“…On the other hand, the dominant PCDD/F congener at Urban Site 2 during LRT, LP, and the normal period was OCDD (26.1%-52.5%), with higher proportion of PCDDs than that of PCDFs during LRT (50.8%) and the normal period (59.9%), when PCDFs dominated during LP (60.2%). The results indicated that OCDD was the dominant PCDD/F congener at all three sampling sites during LRT, LP, and the normal period, which corresponded with findings of Coutinho et al (2007) and Zhang et al (2015). Moreover, the proportion of PCDFs was higher than that of PCDDs at all sites during LRT and LP and increased substantially during LP, largely because of emissions from industrial activity and pollutant accumulation (Lee et al, 2004).…”
Section: Variation Of Atmospheric Pcdd/f Concentrations and Congener mentioning
confidence: 49%
See 1 more Smart Citation
“…On the other hand, the dominant PCDD/F congener at Urban Site 2 during LRT, LP, and the normal period was OCDD (26.1%-52.5%), with higher proportion of PCDDs than that of PCDFs during LRT (50.8%) and the normal period (59.9%), when PCDFs dominated during LP (60.2%). The results indicated that OCDD was the dominant PCDD/F congener at all three sampling sites during LRT, LP, and the normal period, which corresponded with findings of Coutinho et al (2007) and Zhang et al (2015). Moreover, the proportion of PCDFs was higher than that of PCDDs at all sites during LRT and LP and increased substantially during LP, largely because of emissions from industrial activity and pollutant accumulation (Lee et al, 2004).…”
Section: Variation Of Atmospheric Pcdd/f Concentrations and Congener mentioning
confidence: 49%
“…By contrast, Background Site, which was located far from areas of human activities, had the lowest PM 2.5 concentration and PCDD/F concentration. Lower levels of PM 2.5 concentrations and PCDD/F concentrations associated with such geographical locations were also reported in China (Ding et al, 2013), the United States (Cleverly et al, 2007), and Portugal (Cleverly et al, 2007;Coutinho et al, 2007;Ding et al, 2013). PCDD/F concentration levels recorded at all the other sampling sites were lower than those reported in Portugal (49.8 fg I-TEQ m ) but similar to those reported in Argentina (39 ± 76 fg I-TEQ m -3 ) and Taiwan (34-53 fg I-TEQ m -3 ) (Coutinho et al, 2015;Cappelletti et al, 2016;Ho et al, 2016;Lee et al, 2016;Meng et al, 2016;Sun et al, 2017;Xing et al, 2017).…”
Section: Resultsmentioning
confidence: 92%
“…During summer as more heating of daytime than cooling during shortened nights, the convective mixing layer starts shallow in the morning, but rapidly grows to its full extent in early afternoon. On the contrary, during winter as more cooling at night than heating during the shortened daytime, the convective mixing layer remains relatively stable (Coutinho et al, 2007). Hence, local emissions to the atmosphere will be less well dispersed during winter.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio between winter (OctobereMarch) and summer (AprileSeptember) mean values of atmospheric I-TEQ concentrations was 3.90, calculated for the period 2002e2004. Coutinho et al (2007) found the average ratio of the combined PCDD/F concentrations between winter (OctobereMarch) and summer (AprileSeptember) was 3.30 at most. Sin et al (2002) measured 27 ambient air samples in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation